An Examination of the Antecedents and Consequences of Employee Creativity in Indonesian Radio Industry - Santosa, The Elisabeth Cintya; Suharnomo; Yuniawan, Ahyar (The Journal of Behavioral Science, 2022)
Employee creative behavior is a positive behavior needed by organizations to maximize the organization’s ability to achieve its goals. The aim of the study was to analyze factors affecting employees’ creative behavior at work on their performance with perceived organizational support and organizational climate as the antecedents and employee creativity as a mediating variable. The sample was 218 employees, working in broadcasting, production, and marketing divisions, from 27 private’s radio industries in Semarang, Indonesia. Data were collected by questionnaires and analyzed using the structural equation model (SEM). The result showed that the creative behavior of employees increased when the organization provided support to employees (β = .24, p = .00) and organizational climate supported employees developing creative behavior (β = .31, p = .02). The higher the employees’ creativity is, the higher the employees’ performance will be (β = .68, p = .00). Furthermore, our findings showed that employee creativity partially and fully mediated the relationship between POS (β = .35, p= .00) and organizational climate (β = .45, p = .02) with employee performance. The practical implications, especially in improving the creative behavior of employees in the radio industry in Indonesia, is needed to provide support and creating a healthy organizational climate that supports employees to work with creativity, which will ultimately improve their work performance.